Databases focus on terrorism - Arnold, Stephen E (Link-Up (Minneapolis, Minn. 1983), 1992)
Online databases can facilitate scholarly research on a broad range of topics. Terrorism is one example. Terrorism burst upon the national consciousness in the early 1970s and the media covered incidents rapidly and extensively. According to Edna Reid, assistant professor of information science at Rutgers University, as newspaper and television media covered terrorism, there was a corresponding growth in the magazine and journal citations. Then, specialized periodicals and databases developed in response to the new subject area. Today, information about terrorism can be found in most full-text news databases. However, there are 3 databases that provide the most comprehensive information about terrorism: 1. the National Criminal Justice Reference Service, 2. the Library of Congress MARC catalog, and 3. Social Scisearch. For information on terrorists, Reid recommends that individuals supplement information from online databases with printed references, primary materials generated by the perpetrators, and messages from contacts via Internet, Bitnet, Delphi, and similar messaging services.